Traditional Chinese Medicine and Gut Microbiome: Their Respective and Concert Effects on Healthcare - Zhang, Runzhi; Gao, Xi; Bai, Hong; Ning, Kang (Frontiers in Pharmacology, 2020)
Advances in systems biology, particularly based on the omics approaches, have resulted in a paradigm shift in both traditional Chinese medicine (TCM) and the gut microbiome research. In line with this paradigm shift, the importance of TCM and gut microbiome in healthcare, as well as their interplay, has become clearer. Firstly, we briefly summarize the current status of three topics in this review: microbiome, TCM, and relationship of TCM and microbiome. Second, we focused on TCM's therapeutic effects and gut microbiome's mediation roles, including the relationships among diet, gut microbiome, and health care. Third, we have summarized some databases and tools to help understand the impact of TCM and gut microbiome on diagnosis and treatment at the molecular level. Finally, we introduce the effects of gut microbiome on TCM and host health, with two case studies, one on the metabolic effect of gut microbiome on TCM, and another on cancer treatment. In summary, we have reviewed the current status of the two components of healthcare: TCM and gut microbiome, as well as their concert effects. It is quite clear that as the holobiont, the maintenance of the health status of human would depend heavily on TCM, gut microbiome, and their combined effects.